Parasitic behaviour of Dastarcus helophoroides (Fairmaire) (Coleoptera: Bothrideridae) induced changes in free animo acid pools in hemolymph of host Monochamus alternatus Hope (Coleoptera: Cerambycidae) - Li, Xiao-Juan; Dong, Guang-Ping; Fang, Jian-Min; Liu, Hong-Jian; Guo, Wan-Lin (Oriental insects, 2018)
To clarify the impacts of parasitic behaviour of Dastarcus helophoroides on free amino acids concentration of the hemolymph in its host Monochamus alternatus, free amino acids in the hemolymph of M. alternatus larvae were analysed and compared with the composition of larvae parasitised by their main parasitoid D. helophoroides. Forty-eight types of free amino acids were assayed, including 20 amino acids which compose protein and 28 ones which do not compose protein. The amounts of total free amino acids were significantly reduced in parasitised larvae at 48 h post-parasitisation. For the free amino acids which compose protein, parasitism conspicuously increased the contents of cysteine and histidine at 24 h post-parasitisation, as well as the contents of glutamic acid and serine at 72 h post-parasitisation. For the free amino acids which do not compose protein, the concentrations of anserine, homocitrulline and α-aminoadipic acid in parasitised larvae were obviously inhibited at 6 h post-parasitisation. The amounts of phosphorylethanolamine in parasitised larvae were apparently higher than that in the controls at 48 and 72 h post-parasitisation. The content of phospho-serine was also increased in parasitised individuals at 48 h post-parasitisation. The results indicated that parasitic behaviour of D. helophoroides leads to noticeable alterations in levels of free amino acids within the host's hemolymph.